Health Education about Behaviour of Clean and Healthy Life (PHBS) in Household and School - Rahmawati, Anita; Nurmawati, Thatit; Arsa, Sandi Alfa Wiga (STIKes Patria Husada Blitar, 2022)
Enhancement of public health quality through awareness process could be done by behaviour of clean and healthy life (PHBS) program. Application of the PHBS program is determined by knowledge possessed by community toward the program, better knowledge will result on better program awareness implementation. The purpose of this community service is to increase knowledge about PHBS through providing PHBS education. This activity is to be done on two distinct times, places, and targets. The PHBS target on school settings is student of SMKN 2 at the Blitar City, meanwhile the PHBS target on household settings are pregnant women and her companion. Health educations are using lecture and discussion methods with power point presentation and brief video shown by LCD projector. Knowledge measurement before and after education are using questionnaire. Result of this activity are showing average enhancement at knowledge value after education compare with before, both on school settings as well as on household settings. This activity should be continued with focusing on another content of the PHBS program, another target of education or another program level such as at workplace, health facility, or public places.